2021
DOI: 10.2147/jpr.s296540
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Reward System Connectivity Underpins Pain and Emotional Suffering in Migraine

Abstract: Purpose It has been suggested that reward system dysfunction may account for emotion and pain suffering in migraine. However, there is a lack of evidence whether the altered reward system connectivity is directly associated with clinical manifestations, including negative affect and ictal pain severity and, at the molecular level, the dopamine (DA) D2/D3 receptors (D2/3Rs) signaling implicated in encoding motivational and emotional cues. Patients and Methods We acquired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“… 21 Recently, a study focusing on the reward system revealed weaker FC between the right nucleus accumbens and hippocampus in patients with EM. 22 In one study examining the contribution of genotype to hippocampal FC changes in female patients with EM, Liu et al found no significant interaction effect for disease and catechol-O-methyltransferase genotype, but reported decreased FC between hippocampus and multiple brain regions including the mPFC, insula and amygdala in EM patients with val homozygote. 16 Chong et al found stronger structural covariance between the hippocampus and cortico-limbic regions in migraine.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Recently, a study focusing on the reward system revealed weaker FC between the right nucleus accumbens and hippocampus in patients with EM. 22 In one study examining the contribution of genotype to hippocampal FC changes in female patients with EM, Liu et al found no significant interaction effect for disease and catechol-O-methyltransferase genotype, but reported decreased FC between hippocampus and multiple brain regions including the mPFC, insula and amygdala in EM patients with val homozygote. 16 Chong et al found stronger structural covariance between the hippocampus and cortico-limbic regions in migraine.…”
Section: Introductionmentioning
confidence: 99%
“…In subjects with migraine, the amygdala displayed increased rs-FC to middle occipital gyrus (26), middle cingulate cortex (100), right insula (61), and left precuneus (100) compared to HC. Decreased amygdala rs-FC compared to HC was found with orbitofrontal cortex (26), right nucleus accumbens (119), inferior occipital gyrus, and middle occipital gyrus (100). Altered amygdala rs-FC was also demonstrated between different types of migraine: between episodic migraine and chronic migraine (for a number of connected areas) (100), as well as between chronic migraine with and without medication overuse (for FC between bilateral amygdala) (127).…”
Section: Resultsmentioning
confidence: 97%
“…The rs-FC of hippocampus was decreased to some areas (hypothalamus [31], right nucleus accumbens [119], inferior parietal gyrus and supplementary motor area [26]) and increased to other areas (hypothalamus [53], cerebellar and occipital areas [26]) compared to HC. rs-FCD of hippocampus was found increased in chronic migraine (123) as well as decreased in migraine without aura (55) compared to HC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the mesolimbic system (i.e., neurons in the ventral tegmental area that project to the nucleus accumbens [NAc], thalamus, amygdala and hippocampus) and its cortical projections (i.e., to the anterior cingulate cortex, ventromedial prefrontal cortex [vmPFC] and orbitofrontal cortex) are activated in the context of approach and avoidance behaviors, respectively (Cardinal et al, 2002;Salamone, 1994;Salamone & Correa, 2012). Individuals with chronic pain show general deficits in mesocorticolimbic functioning and associated reward processing (Loggia et al, 2014) with the degree of reward system dysfunction correlating with pain severity (Kim et al, 2021).…”
Section: Meditation Practice In Mindfulness-based Treatmentmentioning
confidence: 99%